1999
DOI: 10.1175/1520-0442(1999)012<2747:oqodsa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Objective Quantification of Drought Severity and Duration

Abstract: Common weaknesses of current drought indexes were analyzed. First, most of the current indexes are not precise enough in detecting the onset, end, and accumulated stress of drought. Second, they do not effectively take into account the aggravating effects of runoff and evapotranspiration, which build up with time. Third, they have a limited usefulness in monitoring ongoing drought because they are based on a monthly time step. Fourth, most of them fail to differentiate the effects of drought on surface and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
336
0
25

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 537 publications
(361 citation statements)
references
References 18 publications
0
336
0
25
Order By: Relevance
“…More details on a rather complex calculation procedure of the EDI are available from Byun and Wilhite (1999). Similar to the SPI, the EDI values are standardized, which allows drought severity at two or more locations to be compared with each other regardless of climatic differences between them.…”
Section: The Effective Drought Index (Edi)mentioning
confidence: 99%
“…More details on a rather complex calculation procedure of the EDI are available from Byun and Wilhite (1999). Similar to the SPI, the EDI values are standardized, which allows drought severity at two or more locations to be compared with each other regardless of climatic differences between them.…”
Section: The Effective Drought Index (Edi)mentioning
confidence: 99%
“…The EDI is an attempt to more accurately determine the exact start and end of a drought period. Unlike most drought indices, the EDI in its original form is calculated with a daily time step (Byun and Wilhite, 1996). The EDI is a function of 'precipitation needed for a return to normal' conditions (or to recover from the accumulated deficit since the beginning of a drought), which, in turn, is related to 'effective precipitation (EP)'.…”
Section: Drought Indicesmentioning
confidence: 99%
“…Although this implied that comprehensive research on the spatial and temporal characteristics of droughts over East Asia is necessary, the studies on droughts over East Asia have been very limited so far. Kang and Byun (2001) showed that the 2001 drought in Korea and China was abnormally strong using a daily drought index developed by Byun and Wilhite (1999), but they did not take into account any spatial relationships of drought occurrence and magnitude between the two countries.…”
Section: Introductionmentioning
confidence: 99%